1998
DOI: 10.1111/j.1365-2621.1998.tb15753.x
|View full text |Cite
|
Sign up to set email alerts
|

Singlet Oxygen and Ascorbic Acid Effects on Dimethyl Disulfide and Off‐Flavor in Skim Milk Exposed to Light

Abstract: The light-induced off-flavor and dimethyl disulfide increased as fluorescent light exposure increased from 0, 2, 4, 6, to 8h (PϽ0.05). Sensory evaluation and identified compounds suggest that dimethyl disulfide was mainly responsible for the light-induced off-flavor in skim milk. Dimethyl disulfide was formed by the singlet oxygen oxidation of methionine in milk. Gas chromatographic analysis and sensory evaluation showed that 200, 500, and 1000 ppm ascorbic acid, which is a singlet oxygen quencher, lowered the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
85
0
5

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(92 citation statements)
references
References 23 publications
2
85
0
5
Order By: Relevance
“…In the low fat cheese the accumulation of DMDS was less significant, and a significant difference (P < 0.001) was detected in the levels of generated DMDS between the two types of cheese as well as between the packaging conditions. For the last seven days of incubation (days [14][15][16][17][18][19][20][21], the accumulation of DMDS in the vacuum-packed 18% fat cheeses showed a significant increase (P < 0.001) when compared to the vacuum-packed low fat cheese. The level in the vacuum-packed cheese with 18% fat was comparable to the level of DMDS observed in the low fat cheeses packed in air.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the low fat cheese the accumulation of DMDS was less significant, and a significant difference (P < 0.001) was detected in the levels of generated DMDS between the two types of cheese as well as between the packaging conditions. For the last seven days of incubation (days [14][15][16][17][18][19][20][21], the accumulation of DMDS in the vacuum-packed 18% fat cheeses showed a significant increase (P < 0.001) when compared to the vacuum-packed low fat cheese. The level in the vacuum-packed cheese with 18% fat was comparable to the level of DMDS observed in the low fat cheeses packed in air.…”
Section: Resultsmentioning
confidence: 99%
“…However, more advanced methods have shown that dimethyl disulphide (DMDS) was the major protein oxidation product in milk [19]. DMDS was reported to be mainly responsible for the off-flavour formation in low fat dairy products such as skimmed milk [15], and DMDS has also been detected in low fat cheese [2].…”
Section: Introductionmentioning
confidence: 99%
“…Various techniques have been tested and are used in order to incorporate antioxidants into milk products. Several of these methods are by injecting antioxidants into the cows, adding antioxidants to feeds or the direct addition of antioxidants into final dairy products (Nicholson and Charmley, 1993;Jung et al, 1998;van Aardt et al, 2005a). The bioavailability is greatly decreased when antioxidants are ingested and antioxidant levels will not remain constant as storage of the milk will decrease the antioxidant level (Jensen, 1995;Nielsen et al, 2001).…”
Section: Role Of Iron In Milk Shelf Lifementioning
confidence: 99%
“…Degradation of milk and dairy products represents a significant area of concern for the dairy industry, due to the development of off-flavours, impaired nutritional quality and function. These problems can appear very rapidly under the right conditions, and create consumer complaints (Havemose et al, 2004;Jung et al, 1998;Mestdagh et al, 2005;Østdal et al, 2008). Exposure to heat and/or light, in particular, can result in significant degradation in dairy products.…”
Section: Dairymentioning
confidence: 99%